2021
DOI: 10.1007/s11695-021-05573-w
|View full text |Cite
|
Sign up to set email alerts
|

Structured Lifestyle Modification Prior to Bariatric Surgery: How Much is Enough?

Abstract: Many healthcare systems require patients to participate in a structured lifestyle modification programme prior to bariatric surgery, even though bariatric consensus guidelines do not recommend this. While there is good evidence that such programmes improve health in other conditions such as metabolic and cardiovascular diseases, there is no evidence that they improve outcomes after bariatric surgery. The distinction needs to be drawn between the well-established need for individualised multidisciplinary dietet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 69 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Of the 444 recruited participants, 92 (21%) did not progress to bariatric surgery, with the most frequent reasons given being patient decision or failure to achieve pre-surgery goals. There is limited evidence as to the effect of pre-surgery goals on post-surgery outcomes [133][134][135] and, as these goals are often specific to the individual rather than common across a programme, it is unclear what these goals were for each individual SCOTS participant. Often, goals are to achieve a 5% or 10% pre-surgery weight loss, or are related to maintaining a certain attendance rate at the pre-surgical programme.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 444 recruited participants, 92 (21%) did not progress to bariatric surgery, with the most frequent reasons given being patient decision or failure to achieve pre-surgery goals. There is limited evidence as to the effect of pre-surgery goals on post-surgery outcomes [133][134][135] and, as these goals are often specific to the individual rather than common across a programme, it is unclear what these goals were for each individual SCOTS participant. Often, goals are to achieve a 5% or 10% pre-surgery weight loss, or are related to maintaining a certain attendance rate at the pre-surgical programme.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, systematic reviews and meta-analysis data have demonstrated that receiving LSIs-based on behavioral therapy for obesity (BT-OB)-after surgery determined greater WL than usual care [10]. However, the hypothesis that the same LSI delivered before BS can improve WL outcomes after surgery has not been confirmed [11,12]. A recent systematic review showed no conclusive evidence that intentional WL before BS improved post-operative WL outcomes because of methodological heterogeneity (i.e., not always LSI) and variation in the duration of post-surgical follow-up [13].…”
Section: Introductionmentioning
confidence: 99%